Question 2
Answer: Choice D) (6,4)
When you reflect over the x axis, the x coordinate stays the same while the y coordinate flips in sign (from positive to negative or vice versa)
============================
Question 3
Answer: Choice A) (-5, 6)
The rule (x-2, y+1) means we subtract 2 from the x coordinate and add 1 to the y coordinate. The original x coordinate is x = -3, which then becomes x-2 = -3-2 = -5. The original y coordinate is y = 5 which updates to y+1 = 5+1 = 6. So that's how (x,y) = (-3,5) turns into (x-2,y+1) = (-5, 6)